Gambaran Pengetahuan Tentang Rumah Tunggu Kelahiran Di Tamher Timur - Oktovina Sofiah Rattu; Alfa Fitria (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
The birth waiting home program is listed in the Regulation of the Minister of Health of the Republic of Indonesia Number 82 of 2015 concerning technical instructions for the use of special allocation funds in the health sector and supporting facilities and infrastructure for the health sarpras sub-sector for the 2016 fiscal year in article 5 concerning the operational costs of the birth waiting house. In Indonesia, especially in the archipelago, the mortality rate for pregnant women is still high, thus indicating a low degree of health. This is caused by various factors including geographic, socio-economic factors, limited means of transportation, limited health facilities and health workers. To overcome this, we need a special place close to basic health care facilities or a hospital that can be temporarily occupied by pregnant women before labor arrives called the Home Waiting for Birth (RTK), which has an important function as a temporary residence for pregnant women until they arrive during childbirth. Keywords: Knowledge, Home Waiting For Birth